La traducció d’Antoni Canals del Pater Noster, Ave Maria i Salve Regina: edició crítica a partir d’un nou manuscrit - Casanova, Emili (Revista de Filología Románica, 2010)
In this review it’s offered the critical edition of three Antoni Canals (1352-1419) opuscles, from an unknown until now manuscript found in Naples. It’s the Pater Noster, Ave Maria and Salve Regina translation from Latin which had the purpose of allowing to read this recommended text to the nobility and the bourgeoisie of that historic moment. The edition holds an appendix of variants between both unique manuscripts till now, one per work. It’s one of the linguistically richest texts of medieval catalanovalencian religious literature. It solves some of the hapaxs, for example, níxol, ’stupid’.